2021
DOI: 10.1177/23259671211012393
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sports After Primary Reverse Shoulder Arthroplasty: Outcomes at Mean 4-Year Follow-up

Abstract: Background: With the expanding use of reverse shoulder arthroplasty (RSA) to treat various shoulder conditions, there has been a rise in the number of RSAs performed, especially in physically active patients. Limited information regarding sports after RSA is available to properly counsel patients on postoperative expectations. Purpose: To assess the rate of return to sports as well as the ability to return to the same level of preoperative intensity, frequency, and duration of sport after primary RSA. Study De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…4 The indication for RSA being osteoarthritis or rheumatoid arthritis has been reported to have higher returnto-sport rates than cuff tear arthropathy and fracture (100% vs 76%-81%). 6 Hand dominance did not affect the return-to-sport rate for HA or TSA in 2 studies 5,11 and for RSA in 1 study, 6 but Tangtiphaiboontana et al 18 reported that the laterality of RSA affected return to sport, with a 38% return-to-sport rate after right-sided RSA compared with 71% after left-sided RSA, although the hand dominance of the patients was not specified. Bilateral RSA was reported to have similar return-to-sport rates as unilateral RSA (69% vs 76%, respectively).…”
Section: Risk Factors For Not Returning To Golfmentioning
confidence: 98%
See 3 more Smart Citations
“…4 The indication for RSA being osteoarthritis or rheumatoid arthritis has been reported to have higher returnto-sport rates than cuff tear arthropathy and fracture (100% vs 76%-81%). 6 Hand dominance did not affect the return-to-sport rate for HA or TSA in 2 studies 5,11 and for RSA in 1 study, 6 but Tangtiphaiboontana et al 18 reported that the laterality of RSA affected return to sport, with a 38% return-to-sport rate after right-sided RSA compared with 71% after left-sided RSA, although the hand dominance of the patients was not specified. Bilateral RSA was reported to have similar return-to-sport rates as unilateral RSA (69% vs 76%, respectively).…”
Section: Risk Factors For Not Returning To Golfmentioning
confidence: 98%
“…Bilateral RSA was reported to have similar return-to-sport rates as unilateral RSA (69% vs 76%, respectively). 18 Will Golf Be Painful After Surgery? Three studies 9,11,16 reported details about pain during or after rounds of golf after arthroplasty.…”
Section: Risk Factors For Not Returning To Golfmentioning
confidence: 99%
See 2 more Smart Citations
“…§ However, there are few studies on RTS activity after RTSA. 5,11,25,44,46 From the current studies, it is unclear as to how to predict the probability and appropriate timing of RTS activities after surgery. 13,33 Moreover, the types of sports played are likely to be different across different cultures/ethnicities.…”
mentioning
confidence: 99%